2018
DOI: 10.1051/matecconf/201823702002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silica Powder from Sugar Cane Bagasse Ash and Its Application as Adsorbent in Adsorptive-distillation of Ethanol-water Solution

Abstract: In this study, sugarcane bagasse ash (SCBA) as waste from sugarcane factory was extracted into silica powder. This powder was then used as adsorbent for ethanol purification. Prior to used, the SCBA was washed using HCl solution. The silica extraction was conducted using various NaOH concentrations (0.5; 1; 1.5 and 2 mol/L) as well as extraction times (30, 60 and 90 minutes). After that the mixture was precipitated using HCl solution. The solution was filtrated through a paper filter and its solid particle was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The greatest silica yield was obtained for the silica gel process, 198 g silica/kg SCBA, while the precipitated silica microparticles process provided a yield of 178 g silica/kg SCBA. These silica extraction yields were much lower than others reported for similar biomasses, ranging from 45 to 90% for sugarcane or rice husk ashes, mainly due to the high loss of biomass during the sieving process, which allows the production of 100% biogenic silica [ 9 , 11 , 22 , 25 ].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The greatest silica yield was obtained for the silica gel process, 198 g silica/kg SCBA, while the precipitated silica microparticles process provided a yield of 178 g silica/kg SCBA. These silica extraction yields were much lower than others reported for similar biomasses, ranging from 45 to 90% for sugarcane or rice husk ashes, mainly due to the high loss of biomass during the sieving process, which allows the production of 100% biogenic silica [ 9 , 11 , 22 , 25 ].…”
Section: Resultsmentioning
confidence: 61%
“…Although several works have focused on the production of silica from biomass ashes, particularly from rice husk and sugarcane fly ashes, these materials are commonly assigned to material applications [ 5 , 6 , 7 , 8 ]. Methods for extraction of amorphous silica from sugarcane bagasse ash mostly include acidic pretreatment (mostly with HCl) followed by alkaline extraction with NaOH at 95 ± 5 °C and a precipitation step with HCl to neutralize the solution [ 9 , 10 , 11 ]. These methods allow high-purity silicas (99%) to be obtained, although they lack a finalization step that allows spherical particles suitable for cosmetics to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the NaOH concentration used, the more silica that can be extracted. The research conducted by Megawati [3] showed that 2.0 M NaOH was the optimum concentration for silica extraction from bagasse ash. Likewise, other studies' show that 1.0 M NaOH concentration could extract 91% silica while the NaOH concentration less than 0.1 M was unable to extract silica [11].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the bagasse is used as fuel for heating the boiler. In this process, 8-10% of solid waste is produced in the form of ash [3]. Bagasse ash cannot be used as fertilizer because it is low in nutrients and even increases heavy metals concentration in the soil, for example Al2O3, Fe2O3, MnO, Cr2O3, NiO [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Setyawan et al [25] reported that extraction of biosilica from fresh rice husks (not ashed) resulted in a low extraction yield (9.03%), whereas when ashed, rice husks produced an extraction yield of 62.83% [26]. Megawati et al [27] prepared raw materials by re-ashing sugarcane bagasse ash (SCBA) using a furnace for 3h at 600 o C to reduce carbon content. The extraction yield of re-ashed SCBA was 45.5% at a concentration of 2mol/L NaOH solution with an extraction time of 90min.…”
Section: Introductionmentioning
confidence: 99%